2011
DOI: 10.1038/emboj.2011.359
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-dependent gene silencing involving Ago2-mediated cleavage of a circular antisense RNA

Abstract: MicroRNAs (miRNAs) are B22 nt non-coding RNAs that typically bind to the 3 0 UTR of target mRNAs in the cytoplasm, resulting in mRNA destabilization and translational repression. Here, we report that miRNAs can also regulate gene expression by targeting non-coding antisense transcripts in human cells. Specifically, we show that miR-671 directs cleavage of a circular antisense transcript of the Cerebellar Degeneration-Related protein 1 (CDR1) locus in an Ago2-slicer-dependent manner. The resulting downregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
783
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 881 publications
(807 citation statements)
references
References 49 publications
18
783
0
6
Order By: Relevance
“…Hence, circRNAs were more likely to be implicated within the mechanisms that gave rise to dysfunctional bioactivities, such as the onset and aggravation of cancers. For instance, ciRS‐7, the natural antisense transcript of cerebellar degeneration‐associated protein 1 (CRD1), contained approximately 70 MREs of miR‐7 24, 32, 36. Its high expression within cytoplasms could effectively lower miR‐7 activity through binding to it, thereby down‐regulating the expressions of insulin‐like growth factor‐1 receptor (IGF1R), epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK) 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…Hence, circRNAs were more likely to be implicated within the mechanisms that gave rise to dysfunctional bioactivities, such as the onset and aggravation of cancers. For instance, ciRS‐7, the natural antisense transcript of cerebellar degeneration‐associated protein 1 (CRD1), contained approximately 70 MREs of miR‐7 24, 32, 36. Its high expression within cytoplasms could effectively lower miR‐7 activity through binding to it, thereby down‐regulating the expressions of insulin‐like growth factor‐1 receptor (IGF1R), epidermal growth factor receptor (EGFR) and focal adhesion kinase (FAK) 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Weinmann et al detected AGO2 in the nucleus of HeLa cells (Weinmann et al, 2009). Notably, it has been shown that Argonaute proteins are directly associated with nuclear miRNAs in Caenorhabditis elegans (C. elegans) (Zisoulis et al, 2012) and human cells (Hansen et al, 2011;Zisoulis et al, 2012). Because Argonaute proteins are the catalytic center of RISC, their presence in the nucleus may imply that they have biological relevance in the nucleus.…”
Section: Protein Cell and Presence Of Argonaute Proteins In The Nucleusmentioning
confidence: 99%
“…The fi nding that significant amounts of mature miRNAs are localized in the nucleus (Meister et al, 2004;Politz et al, 2006;Hwang et al, 2007;Foldes-Papp et al, 2009;Liao et al, 2010;Jeffries et al, 2011) raises the interesting possibility that miRNAs may function as gene regulators in the nucleus, through a mechanism other than classic post-transcriptional repression. Indeed, recent studies by our (Tang et al, 2012) and other research groups (Hansen et al, 2011;Zisoulis et al, 2012) demonstrate that some miRNAs can act in an unconventional manner to regulate the biogenesis and function of ncRNAs, including miRNAs and long ncRNAs. These intriguing discoveries lead to a novel model of miRNA function and add new complexity to the gene regulatory network.…”
Section: Introductionmentioning
confidence: 99%
“…The CDR1as/ciRS-7 circular RNA contains a near perfect miR-671 target site that can be cleaved by Ago-2 to trigger transcript degradation. 56 This, however, appears to be an isolated mechanism, as no other circular RNA is known to contain similar sequences that induce Ago-2 slicing. Roles for other RNA endonucleases in circular RNA decay have not yet been explored.…”
Section: Circular Rna Degradationmentioning
confidence: 99%
“…This was the first hint that the dominant output of a gene could, in some cases, be a circular RNA rather than a linear mRNA. 48 A handful of additional circular RNAs were identified over the ensuing years [49][50][51][52][53][54][55][56] until deep sequencing efforts combined with new computational algorithms all of a sudden revealed thousands of previously missed circular RNAs from eukaryotic cells. 13,14,27,29,31,33,40,57,58 Over 25,000 putative circular RNAs, derived from »15% of actively transcribed genes, were identified in human fibroblasts alone.…”
Section: Introductionmentioning
confidence: 99%